Need for Determining the Effects of Sulphur Fertilization on the Amounts of Organic Sulphur Compounds in Plant Foods - Prasad, Rajendra; Shivay, Yashbir Singh (International Journal of Bio-resource and Stress Management, 2021)
A large number of field trials are being conducted in India and across the globe on the yield response and uptake of sulphur (S) in a number of crops and most results show a good yield response. However, none of the studies bring out the effect of S fertilization on S containing amino acids viz. cysteine, methionine and vitamin like Thiamine, which are essential for human life and are to be obtained only from plant foods. It is due to lack of awareness and also poor infrastructures in terms of biochemical analysis of the agricultural produce in most of the developing countries including India. Therefore, there is an urgent need to establish food quality analysis laboratories in the leading institutes of the country for initiating analysis of plant foods for S-containing organic compounds